Student Perception of "A" Fighting Workshop for Digital Information Technology (Digital Technology) Program PSMZA - Norhafiza Binti Idris; Noor Rulhanim Binti Mohamad Ariffin (Jurnal Konseling dan Pendidikan)
Programme of study Diploma in Information Technology (DDT) provides education and training in the field of computing with specific emphasis on the areas of Information Technology. In order to ensure technology development in line with the needs of industry, Department of Polytechnic Education (JPP) have checked the curriculum Diploma of Information Technology (Digital Technology). Curriculum Diploma of Information Technology (Digital Technology) has set a 40% as a pass score for Discrete Mathematics course (DBM2033) in the assessment of coursework and final examination. However, students who take courses in Discrete Mathematics (DBM2033) is weak in terms of calculation and this resulted in their results less impressive in this course. This continuity, a Bengkel Gempur “A” for the Diploma of Information Technology (Digital Technology) was implemented. This research in the form of surveys and applying data obtained from the questionnaire. The samples consist of 54 semester two students who take courses in Discrete Mathematics (DBM2033) for session June 2017. Pilot study of reliability value α = 0.930. The findings of this study show the level of students ' perception of Bengkel Gempur “A” are at a high level and students have a positive perception after following the workshop. However, the findings show there is no difference in perception among the students based on the demographics of the respondents, i.e. gender, race, age, education status and cumulative grade points average (CGPA). Students ' perception on the Bengkel Gempur “A” has changed since joining the program. This has proved through score mean before the programme was 2.28 and mean score after participating in the programme was 2.96 which increased by 0.68. This study demonstrated that the implementation of Bengkel Gempur “A” has managed to increase the level of student achievement onfinal examination sessions June 2017.